2022
DOI: 10.7759/cureus.23719
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Physical Inactivity and Obesity in the Urban Slums of Lahore

Abstract: Introduction There are several factors such as physical inactivity, sedentary lifestyle, and diet that can be responsible for weight gain or obesity. Regular physical activity is important for better physical and emotional well-being. The objective of the study is to observe the prevalence of obesity or over-weight and how lack of physical activity contributes to weight gain and other health issues. Methods This cross-sectional study was conducted in Shalamar Town, Lahore on 64… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
2
1
0
Order By: Relevance
“…Although previous research has indicated a link between age and obesity [16], our study did not observe a signi cant association, potentially due to our careful matching of subjects based on age. Nevertheless, our ndings regarding the correlation between obesity and habits such as consuming an additional meal (the "4th meal") and exhibiting obsessive eating behaviors (eating every hour) align with earlier studies [17]. It has been widely recognized that frequent and compulsive consumption of carbohydrate and fat-rich foods can lead to increased fat deposition and central obesity, particularly in older individuals, as levels of anabolic lipolytic hormones like growth hormone (GH) and sex steroids gradually decline with age.…”
Section: Association Of Lifestyle and Medical Factors With Obesitysupporting
confidence: 90%
“…Although previous research has indicated a link between age and obesity [16], our study did not observe a signi cant association, potentially due to our careful matching of subjects based on age. Nevertheless, our ndings regarding the correlation between obesity and habits such as consuming an additional meal (the "4th meal") and exhibiting obsessive eating behaviors (eating every hour) align with earlier studies [17]. It has been widely recognized that frequent and compulsive consumption of carbohydrate and fat-rich foods can lead to increased fat deposition and central obesity, particularly in older individuals, as levels of anabolic lipolytic hormones like growth hormone (GH) and sex steroids gradually decline with age.…”
Section: Association Of Lifestyle and Medical Factors With Obesitysupporting
confidence: 90%
“…In line with research conducted by Kazmi et al, (2022) that as many as 66.6% of respondents who did not do moderate physical activities such as cycling, aerobics, and other light sports, were overweight or obese. According Yeşilçiçek Çalik et al, (2018) said that being overweight and obese in the preconception period causes gestational diabetes, hypertensive disease, premature labor, induction of birth, birth complications, increased cesarean delivery, postpartum hemorrhage, thromboembolism, breastfeeding problems, and depression.…”
Section: Body Mass Index (Bmi)supporting
confidence: 84%
“…Their research, involving 646 participants, spanned from September 2018 to September 2019. Results from the one-year follow-up revealed a noteworthy correlation between rising BMI and sedentary behavior, particularly among females who exhibited higher rates of overweight and obesity [135].…”
Section: The Impact Of Physical Activity and Its Lack On Obesity And ...mentioning
confidence: 92%
“…Additionally, resistance exercise has demonstrated its effectiveness in contributing to weight management [133,134]. Kazmi et al [135] conducted a study to assess the prevalence of obesity and overweight stemming from sedentary lifestyles in the urban slums of Lahore, Pakistan. Their research, involving 646 participants, spanned from September 2018 to September 2019.…”
Section: The Impact Of Physical Activity and Its Lack On Obesity And ...mentioning
confidence: 99%